Mutations of the CHEK2 gene in patients with cancer and their presence in the Latin American population (2016)
Background: CHEK2 (Checkpoint Kinase 2) encodes CHK2, a serine/threonine kinase involved in maintaining the G1/S and G2/M checkpoints and repair of double-strand DNA breaks via homologous recombination. Functions of CHK2 include the prevention of damaged